INTERSUBJEKTIVITAS WAJAH DAN TANGGUNG JAWAB HUMANITER: MENYIKAPI AMORALITAS PERANG - Simon Pedro Pitang; F. X. Eko Armada Riyanto; Mathias Jebaru Adon (Sanjiwani: Jurnal Filsafat, 2025)
The research focuses on exploring the meaning of Emanuel Levinas' ethics of face in illuminating the immorality that occurs in war. For Levinas, humans are "being-for-the-other"; beings who exist in the world for others. Levinas proposes how "being-for-the-other" always has the nature to be responsible for the presence of other humans with sorge (care). On the other hand, humans often become power-hungry "animals", which can only be obtained if they conquer others, especially in this case, is war. Humans are increasingly showing a life of utter disregard for other human beings by constantly waging war. Therefore, exploring facial ethics and humanitarian responsibility according to Levinas' thought will find intersubjective attitudes that humans can internalize to realize other humans as existences who also have experiences and feelings, are valuable and precious. The method used in the research is qualitative method through literature study. This research found that face ethics gives intersubjective understanding to every human being. The contribution of this research is to understand that war is immorality; which is the destructiveness of humanity that violates the principles of intersubjectivity and humanitarian responsibility.